THE USE OF DECORATIVE TILE-COVERED THERMAL PANELS FOR BUILDING FAÇADE INSULATION - Mirzakulov Islomjon Xoljigitovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This paper explores the advantages of using tiled thermal panels in modern construction. These panels combine insulation, durability, and aesthetic value, making them ideal for energy-efficient and visually appealing buildings. The integration of traditional Uzbek ceramic designs into modern thermal panel systems offers a unique blend of national identity and contemporary architectural needs. Tiled thermal panels are cost-effective, environmentally friendly, and suitable for various building types, highlighting their potential as a practical local construction material.